(untitled) (Hematology Meeting Reports, 2009)
Hodgkin lymphoma (HL) is one of the most treatable adult cancers, with long-term cure rates of more than 80% achieved even in patients with advanced disease.1,2 The combination of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD), is currently considered to be the standard treatment for HL worldwide.3 As an improvement on the ABVD combination, other regimens, including Stanford V, MOPPEBVCAD, EVA, VEBEP, and ChlVPP/ABVVP, have been proposed but none have so far been demonstrated to be more effective than ABVD.4-9 In 1990, the German Hodgkin Study Group (GHSG) developed a dose-escalated and accelerated combined modality regimen consisting of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPP), plus radiation therapy (RT). The HD9 trial compared cyclophosphamide, vincristine, procarbazine, and prednisone, plus doxorubicin, bleomycin, vinblastine, dacarbazine (COPP/ABVD) with both standard BEACOPP and escalated BEACOPP. This trial demonstrated the superiority of escalated BEACOPP, both in terms of failure free survival (FFS) and overall survival (OS).10 Concern about the toxicity of BEACOPP has been raised, however, and further trials designed to identify a therapy with the best risk-to-benefit ratio have been initiated by several Cooperative Groups. One trial by the European Organization for Research and Treatment of Cancer (EORTC) is currently recruiting and randomizes patients with advanced HL between 4 escalated plus 4 standard courses of BEACOPP versus 8 courses of ABVD.